Process of affectivity and learning in Early Childhood Education: the context of a Nursery in Northeast Pará (Research, Society and Development, 2023)
This work aims to analyze how affectivity has been considered by early childhood education teachers, as it is understood that affectivity in early childhood education is relevant to the child's development. Therefore, it was necessary to carry out a questionnaire with teachers who work in early childhood education, specifically in 2 and 3 year old classes at a daycare center in northeastern Pará. In addition, this research has a qualitative character. The results showed that the teachers understand the importance of affection in the school context and that they use this aspect as a facilitator in the classroom routine to establish an affectionate relationship with the students. Therefore, it is possible to say that affectivity will somehow influence the learning process and thus make it more enjoyable for children, in addition, an affectionate relationship between teacher and student makes the environment more welcoming and conducive to awakening the interest of the child. child in learning.